Dementia Care An Evidence-Based Approach - Boltz, Marie; Galvin, James E. (Springer International Publishing : Imprint: Springer, 2016)
This book provides an overview of the demographic, clinical, and psychosocial context of dementia care. With its focus on patient and family perspectives, this book describes evidence-based approaches towards prevention, detection, and treatment of dementia that is unlike any other book. The text presents memory clinics, care management, home-based interventions, palliative care, family caregiver programs, specific to dementia care. Additionally, the text examines strategies to support transitions to acute care and long-term care. The text also places a special emphasis on measures of quality, cultural sensitivity, and implications for health care policy. Written by experts in the field, Dementia Care: An Evidence-Based Approach is an excellent resource for clinicians, students, healthcare administrators, and policymakers who aim to improve the quality of life of both the person with dementia and their informal caregiver. .